Is the ‎Islamic unit trust market efficient empirical evidence from ‎Malaysia‎ - Othman, Anwar Hasan Abdullah; Abd Aziz, Hassanuddeen; Kassim, Salina (Institutional Investor, Inc, 2018)
Based on Malaysian data covering the period from April 2006 to December 2015, this study investigates the informational efficiency of the Islamic unit trust market. The study considers various types of Islamic unit trust funds and analyses their relationship with selected macroeconomic variables. The Engle and Granger (1987) and Granger (1969) causality tests are applied to seven models comprising different types of Islamic unit trust funds. Results show that Islamic equity, balance, fixed, and Feeder Funds violate the efficient market hypothesis (EMH), while the Islamic bond, mixed, and money market funds hold for the weak form of EMH. This provides empirical evidence to fund managers and unit-holders considering market efficiency in strategising their trading proficiency in UTFs. These findings also enable authorities to take steps towards improving funds disclosure practices, so that fund prices immediately reflect relevant information.